#TITLE_ALTERNATIVE# - Arianto Tampubolon (NIM : 15112016), Daniel
<palign="justify">In the past few years, some Global Positioning System (GPS) receivers have been produced and marketed in low price. In this final project some low-cost GPS receivers, such as u-blox 6H, u-blox M8T, and Tersus Precis BX305, are introduced and tested for their potential in performing precise positioning. In this study the kinerjance was assessed with the receiver noise. The tests were performed using two high-cost GPS receivers, the Topcon NET-3GA and Astech ProFlex 500, as reference for the zero-baseline double-difference method. Spectrum and autocorrelation analyzes were performed on double-difference residual data to detect the presence of systematic errors and the receiver noise characteristics. From the study it was found that the measurements of pseudorange tend to contain systematic errors. Low-cost GPS receivers perform competitively in measurements of pseudorange with difference of residual standard deviation about 15 cm against it in the high-cost receiver. Improvement can be gained by using similar receivers. Low-cost receivers do not have any significant difference from high-cost receivers in the measurement of carrier phase.<palign="justify">